İLERİ YAŞ BAŞAĞRILARI - KARAALİ SAVRUN, Feray; SAVRUN, Mert; SAİP, Sabahattin (Cerrahpaşa Medical Journal, 2019)
Background.- In this case group, we try to describe the features of headache in headache out-patients population aged 50 years or more. Design.- The database of patients admitted to Cerrahpaşa Headache Clinic between 1994-1996 was used according to the International Headache Society (IHS), 1988 criteria. Results.- The study included 238 cases (age range:50-83). Mean age at onset of headache was 45.1 (range: 8-83).One hundred-three of these cases had an onset age≥50 (mean: 57.7) with 70.8% female. In the whole group 43% had migraine, 35% had tension-type headache (TTH) and 7% had chronic daily headache, while %5.5 had secondary type of headache such as temporal arteritis, brain tumor, and %6.8 had unclassified head pain. Conclusion.- New onset of primary headache frequency decreases in this population. Comorbidity of depression and primary headaches and, secondary headaches increase relatively in the elderly population.